Is there an HbA1c Threshold for Symptoms of Chronic Hyperglycemia? - Müller, Nicolle; Lehmann, Thomas; Müller, Ulrich Alfons; Kloos, Christof (Experimental and Clinical Endocrinology & Diabetes, 2021)
Aims of the study The minimum therapeutic goal regarding metabolic control for people with diabetes mellitus is the “absence of symptoms of hyperglycemia.” However, it is uncertain whether a level of HbA1c can be defined that guarantees the absence of these symptoms. The aim was to define an HbA1c threshold above which most patients show hyperglycemic symptoms.Methods In a multicenter cross-sectional study, 137 patients with type 1 and 285 with type 2 diabetes were asked about their symptoms during periods of hyperglycemia with a standardized questionnaire. Seventeen symptoms of hyperglycemia were summarized to the total hyperglycemia symptom score (THSS; min. 0; max. 68). The answers could be given according to the frequency and intensity in the last 4 – 6 weeks.Results The HbA1c threshold above which most patients showed hyperglycemic symptoms was 10.05% for patients with diabetes type 1 and 8.9%. for patients with type 2. Most confidence was reached on the symptoms of frequent urination” and “tiredness.” The mean THSS was 19.4 (±9.0) and showed a positive correlation with age (r=0.167; p<0.001) and HbA1c (r=0.254; p<0.001).Conclusions We identified an HbA1c threshold above which most patients show symptoms of hyperglycemia. In the treatment of people with diabetes mellitus, a safety margin to this threshold should be maintained to preserve well-being and avoid distress. However, since hyperglycemia symptoms are subject to many influencing factors, an adjustment of the therapy—both intensification and de-intensification—should always be carried out in combination with the requested hyperglycemia symptoms and HbA1c value.
Keywords: diabetes mellitus; symptoms hyperglycemia; HbA1c